POTENCY OF MAKASAR FRUIT EXTRACT (Brucea javanica L. Merr) AS AN ANTIBACTERY OF Escherichia coli - Ayu Wulandari; Abdul L. Mawardi (BIOEDUKASI, 2021)
The fruit of Makasar (Brucea javanica L. Merr) is a shrub that grows wild in forest areas and is also planted as a hedge plant. This fruit contains antibacterial compounds that inhibit the growth of Escherichia coli bacteria. This study aims to determine the potential for extracts and to determine the concentration of the fruit extract of Makasar (Brucea Javanica L. Merr) which has the potential as antibacterial Escherichia coli. Makasar fruit extract (Brucea javanica L. Merr) was obtained by maceration method using 96% ethanol as solvent. This study uses the disc diffusion method. The parameter measured is the size of the extract inhibition zone. The results analysis One-way ANOVA of the research on the fruit extract of Makasar (Brucea javanica L. Merr) have the potential as an antibacterial agent for Escherichia coli as evidenced by the value of Fcount > Ftable (28.370 > 2.85). The maximum zone of inhibition was at the concentration of P6 (15.33) and the zone of minimal inhibition was at the concentration of P1 (7.33). It can be concluded that the fruit extract of Makasar (Brucea javanica L. Merr) has antibacterial potential with strong criteria at P6 (15,33), P5 (14,47), P4 (14,03), P3 (13,57), and for moderate criteria at P1 (7,33) and P2 (9,17).